PENGARUH KOMPENSASI, PENGEMBANGAN KARIER DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT.PERKEBUNAN TUNGGAL MITRA PLANTATION MANGGALA 2 - Bate’e, Yuniar; Sinaga, Ria Veronica (UNIKA Santo Thomas, 2019)
This study aims to examine and analyze the effect of compensation, career development and work discipline on employee performance at PT. Perkebunan Tunggal Mitra Plantation Manggala 2. Data collection was carried out through questionnaires carried out on 50 employees of the production department at PT Perkebunan Tunggal Mitra Plantation Manggala 2. Data analysis in this study used SPSS Version 22. The sampling technique used was the saturation sampling method and Data analysis method used is multiple regression analysis (multiple regression analysis). Based on the results of the study, obtained the following regression equation: Y = 9,944 + 0.390X1 + 0.115X2 + 0.267X3 + ei means that the F Test shows that compensation, career development, and work discipline have a positive and significant effect on employee performance. Based on statistical data analysis, the indicators in this study are valid and the variables are reliable. Partially (t test) shows that compensation has a positive and significant effect on employee performance (tcount 4.223> t table 1.675 and a significant level of 0.000 t table 1.675 and a significant level of 0.010 t table 1.675 and a significant level of 0.042